Patients With Deep Ovarian Suppression Following GnRH Agonist Long Protocol May Benefit From a Modified GnRH Antagonist Protocol: A Retrospective Cohort Study - Liu, Shan; Liu, Minghui; Li, Lingxiu; Li, Huanhuan; Qu, Danni; Ren, Haiying; Su, Hui; Zhang, Yang; Li, Yuan (Frontiers in Endocrinology, 2021)
Objective: To verify if patients with deep ovarian suppression following gonadotropin releasing hormone (GnRH) agonist long protocol may benefit from a modified GnRH antagonist protocol based on luteinizing hormone (LH) levels. Design: Retrospective cohort study. Setting: University-based hospital. Patients: 110 patients exhibited ultra-low LH levels during ovarian stimulation using GnRH agonist long protocol. Intervention(s): As all the embryos in the first cycle were exhausted without being pregnant, these patients proposed to undergo a second cycle of ovarian stimulation. 74 of them were treated with a modified GnRH antagonist protocol based on LH levels. Other 36 patients were still stimulated following GnRH agonist long protocol. Main outcome measure: The primary outcome was live birth rate (LBR). The second outcomes were biochemical pregnancy rate, clinical pregnancy rate (CPR), ongoing pregnancy rate (OPR) and cancellation rate. Results: Reproductive outcomes were much better in the modified GnRH antagonist protocol. The OPR and LBR were much higher in the GnRH antagonist protocol group than in the GnRH agonist long protocol group [odds ratio (OR) 3.82, 95% confidence interval (CI) 1.47, 10.61, P=0.018; OR 4.33, 95% CI 1.38, 13.60, P=0.008; respectively]. Meanwhile, the cancellation rate was much lower in the GnRH antagonist protocol group (OR 0.13, 95% CI 0.02, 0.72; P=0.014). Mean LH level during stimulation did not have a predictive value on live birth. However, it was independently associated with the occurrence of ongoing pregnancy (OR 2.70, 95% CI 1.25, 5.85; P=0.01). The results of sensitivity analyses were consistent with the data mentioned above. The patients got completely different and excellent clinical outcomes in their second cycles stimulated with the modified GnRH antagonist protocol. Conclusion: Patients with deep ovarian suppression following GnRH agonist long protocol may benefit from a modified GnRH antagonist protocol based on LH levels.